Madelung disease (multiple symmetric lipomatosis) - Maximiano, Linda Ferreira (Autops Case Rep, 2018)
Madelung disease or multiple symmetric lipomatosis (MSL) is a rare entity among the overgrowth syndromes. It is characterized by painless non-encapsulated and symmetric fatty deposits in the neck, torso, mammary, and abdominal areas, and in the upper and lower limbs. The etiology of the disease is still unknown. Chronic alcohol consumption may play a role in adipocyte hyperplasia in genetically susceptible individuals. Besides the overgrowth of adipose tissue, patients with MSL present features of metabolic syndrome. Patients seek medical attention usually for esthetic reasons. We present the case of a middle-aged man who sought the outpatient clinic complaining of bulging masses in the posterior upper part of the thorax, the occipital area, and the neck. The masses grew over a period of 2 years. The physical examination and imaging study revealed the presence of symmetric lipomatosis. A two-step surgical treatment was undertaken for the excision of the lipomatous tissue. The postoperative outcome was uneventful with satisfactory esthetic results.